Morphological Variation of Somatic Embryos of Coffea arabica L. During Some Sub-Culture Periods - Fitria Ardiyani; Sulistyani Pancaningtya (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
One of factors that affects the success of a plant cultivation using somatic embryogenesis method is the formation of somatic embryos from embryogenesis callus. This research aimed to study the effect of sub-culture period on quality and quantity of the somatic embryos of Coffea arabica. This research used explants of somatic embryos of Arabica coffee obtained from the leaves of 2K Andungsari clone. The embryos were taken during embryogenes is callus phase using Murashige-Skoog culture media added with B5 vitamin and auxin hormone (2,4dichlorophenoxy acetic acid) 0.5 mg/L and sitokinin (benzyl amino purin) 1 mg/L. Observation on somatic embryos obtained from the sub-culture period of 3, 6, 9, 12 and 15 weeks. The parameters observed in this study included quantity and quality of the somatic embryos during each sub-culture period. Observations on quantity of the somatic embryos were conducted based on number of embryos per cluster, while quality was measured from the percentage of normal embryos, histological analysis, and morphological measurement on weight and size of the normal embryos. The result showed that the best quantity of somatic embryos was obtained from the sub-culture period of nine weeks with 18.4 somatic embryos per cluster. The best quality embryos were also obtained in the sub-culture period of nine weeks with the percentage of normal embryos 71.4%. Histological analysis carried out on the somatic embryos obtained from sub-culture of three weeks period showed that the cells of the embryos were formed by living and solid cells which nucleus were clearly seen in the center of the cell, indicating that the embryos were formed by young tissues. Data of morphological parameters showed that normal embryos during the sub-culture period 3 to 15 weeks weighed around 0.23–0.78 mg and length of around 0.18–0.25 cm. The data can be used to predict number of explants and required time to produce certain number of normal embryos